IMPLEMENTASI NILAI SIPAKATAU, SIPAKALEBBI, DAN SIPAKAINGE DALAM PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Reski Amalia; Ardhi Prabowo; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The erosion of local cultural values in formal education systems has become a critical issue in the globalization era. This study aims to analyze the implementation of sipakatau (mutual humanization), sipakalebbi (mutual respect), and sipakainge (mutual reminder) values in elementary students' character formation. Using a qualitative descriptive approach with a case study design in two elementary schools in South Sulawesi, data were collected through participatory observation, in-depth interviews, and document analysis over four months. Findings reveal that these values are implicitly implemented in school culture but lack formal curricular integration. This research contributes a conceptual model for integrating local values into contextual, wisdom-based character education.